Patient-reported outcomes on gastrointestinal tolerance and adherence to a pea protein plant-based enteral formula in children and adults - Cohen, Stanley A.; Millovich, Vanessa; Newman, Dwan; Withrow, Nicole; Beseler, Lucille; Valentine, Christina J. (Frontiers in Nutrition, 2025)
IntroductionEnteral Nutrition through a feeding tube or orally can improve patient outcomes when tolerated to achieve nutritional requirements. While experts have provided feeding guidelines to enhance safety and efficacy, challenges in gastrointestinal (GI) tolerance such as diarrhea, constipation, bloating and vomiting often complicate adherence. Problems such as malnutrition, morbidity, and mortality occur when gastrointestinal intolerance results in the provision of formulas stopping and starting, and therefore delays, in optimal intake. Formulas vary widely in their composition, including differences in the primary protein source, degree of protein hydrolysis, inclusion of common allergens, fiber content, use of artificial or nonnutritive sweeteners, and use of artificial colors. A distinctive yellow pea protein, plant-based enteral formula (PPPBF) that includes fiber, and is free from common allergens and artificial and nonnutritive sweeteners may improve tolerance and adherence.MethodsWe examined the patient or caregiver reports of gastrointestinal (GI) intolerance and adherence in both pediatric and adult participants using two electronic surveys. The initial survey compared pre and during utilization of the PPPBF and the second survey, sent 12 months later, evaluated the same reported outcomes, specifically on the use of a PPPBF.ResultsThere were 392 respondents to the initial survey [n = 160 Pediatric (< /=19 years); and n = 232 Adults (>/=20 years)]. A positive trend toward GI tolerance and adherence was observed.ConclusionA PPPBF with fiber may promote enteral tolerance and support nutritional intake. If used as a first-choice formulation option, it may reduce formula switching that often results from GI intolerance.